Sistem E-Commerce Indekost Terintegrasi dengan Web Geographic Information System - Tari, Gunawan; Putri, Iin Karmila; Jumardi, Andi (SAFE-Network, 2025)
Currently, students and the public in searching for boarding house information only rely on information from friends, relatives or manual searches to find the availability of boarding houses. Currently, the availability of information service platforms for boarding houses is now numerous, especially those based on websites and Android-based. Boarding house information services based on websites and Android-based only provide general information related to boarding house information, but are not able to provide comprehensive information. The purpose of this study is to contribute to the field of information technology through innovation in the development of an e-commerce platform Indekost integrated with the Web Geographic Information System that can help improve information accessibility, facilitate the boarding house search process and ultimately increase user satisfaction in choosing boarding houses that suit their needs. The type of research used is Research and Development (R&D) using the waterfall development model. The results of this study were able to produce an e-commerce application product Indekost that is able to integrate with the Web Geographic Information System. The results of black-box testing showed that all menus can function properly and according to expectations. The results of expert testing and user testing obtained a final score of 3.8, meaning the assessment falls into the very appropriate category.